Diabetes - the global picture: the world’s greatest public health challenge - Zimmet, Paul (Henry Stewart Talks, 2013)
UN recognition of diabetes, Obesity and Diabesity, Modernization and high diabetes prevalence, Age specific prevalence of diabetes: Nauru, The 10 top nations for diabetes prevalence: 2010, Global epidemic of type 2 diabetes prediction, Undiagnosed diabetes, Increasing diabetes prevalence in China, The sugar disease in India, The Middle-East: world diabetes hot-spot, Diabetes prevalence in Qatar, Australia, Japan, Diabetes increase in rural communities, AusDiab mortality follow-up, Diabetes in indigenous Australians, Type 1 diabetes in the young, Population based diabetes register, Childhood diabetes incidence and trends, Type 1 diabetes incidence in Finnish children, Incidence of diabetes in end-stage renal failure, Age of death: general population vs. diabetes, Mauritius surveillance study, First study in a developing country, Predictors for CVD deaths, Genetic-environment interaction, Epigenetics: a new paradigm for prevention, Developmental plasticity, Diabetes prevalence in Cambodia, Poverty and diabetes